Relationship Between Multiple Intelligence and Career Interest Among Secondary Schoolstudents. - Azriah Mohd Azmi; Ku Suhaila Ku Johari; Izwan Mahmud (RedwhitePress)
Intelligence is one ability to respond successfully to a new situation and the capacity to learn from one’s past experiences. While interest is a strong motivation that drives actionsand determined by personality factors. This study aims to observethe relationship between multiple intelligence and career interests among secondary students. It used correlation methodto identify the relationship between multipleintelligence variables and career interests.All 77 Form Three students were involved in this study. The research instruments used were Multiple Intelligence Inventory and Career Interest Inventory. This data was analysed by using a Pearson statistical correlation type of SPSS Version 23. The finding of this study shows that there isa moderate and significant relationship between multiple intelligence and career interest. This finding also shows that the higher intelligence range, the more congruent personality patterns. This implies the tendency of personality patterns as a predictor of emotional intelligence. Further studyis suggested to usean appropriate and structured intervention in research methodology.